Narrating Diasporic Religion and Postsecular Identity in Tahar Ben Jelloun’s A Palace in the Old Village - Abdelaziz El Amrani (Religions)
Inspired by Western secular literary tradition, many diasporic writers in the Maghreb in general and in Morocco in particular did not include religious or spiritual themes in their literary works, as compared to the valorized ones of race, class and gender. Much of Maghrebian fiction, primarily written by immigrant writers of Islamic background who adopt secular perspectives that are often critical of Islam, has depicted religion, especially Islam, in negative terms. Tahar Ben Jelloun is one of those writers who are criticized for being self-orientalizing authors who ‘prostitute’ their works to their Western audience. But, Tahar Ben Jelloun is misunderstood by the majority of his readers. In this article, using postsecularism and secular spirituality as analytical tools, I will explore the postsecular identity and diasporic religion in Tahar Ben Jelloun’s A Palace in the Old Village. Reading the novel from a postsecular perspective and more specifically from a secular spiritual perspective, I will show that Tahar Ben Jelloun is neither self-orientalizing Islam nor celebrating French secularism. Instead, he is upholding postsecular values and diasporic consciousness by negotiating instances of extremism and communalism that mark the failures of both organized religion and Eurocentric secularism. Indeed, Ben Jelloun presents Islam as faith, as a spiritual practice; a diasporic religiosity which is not associated with any political doctrine or organization.